EXTENDING THE FAMILY 500+ PROGRAMME – A CRITICAL ANALYSIS - KRAWCZYK, MICHAŁ (Management and Administration Journal, 2021)
Starting from April 2016, the Polish government introduced a new type of social benefit - the child-rearing benefit. Initially, it was granted to the second and subsequent children, and in the poorest families, to the first one. The Act of 26 April 2019 amending the Act on State Assistance in Upbringing Children as well as certain other acts extended, from 1 July 2019, the validity of the "Family 500 +" programme to every child under 18 years of age, regardless of the family income criterion. The study analyses the underlying assumption and aim of the reform, and also attempts to answer the question: to what extent has broadening of the Family 500+ programme brought the expected results?